Could the connectedness of primary health care workers involved in social networks affect their job burnout? A cross-sectional study in six counties, Central China - Yiqing Mao; Hang Fu; Zhanchun Feng; Da Feng; Xiaoyu Chen; Jian Yang; Yuanqing Li (BMC, 2020)
Abstract Background This study aimed to reveal the effects of the connectedness of primary health care (PHC) workers in social networks on their job burnout. Methods Cross-sectional survey data of rural PHC workers in China were analyzed. A total of 663 respondents were enrolled. Chi-square and cumulative logistic regression were used to determine the effects of the connectedness of PHC workers in social networks on their job burnout. Results PHC workers in rural China had high levels of emotional exhaustion (24.1%), depersonalization (15.7%), and lack of personal accomplishment (34.7%). More than half of the participants were in the middle connectedness level in terms of their advisory (70.4%) and friendship (70.3%) networks. The degree of emotional exhaustion seemed to increase when participants had a low connectedness in their friendship networks (β = 0.769, 95% CI = 0.080-1.458, P = 0.029). Respondents with the middle level of connectedness in advisory networks had higher levels of depersonalization (β = 0.739, 95% CI = 0.130-1.348, P = 0.017) and lack of personal accomplishment (β = 0.583, 95% CI = 0.111-1.055, P = 0.015) than those with the high degree of connectedness in advisory networks. Conclusions The connectedness of PHC workers in social networks influenced their job burnout. Thus, organizations should establish an informal communication platform and information feedback mechanism, promote and manage friendship networks, and help PHC workers overcome emotional exhaustion. Managers should also encourage individuals with a high level of connectedness in advisory networks play the role of "opinion leader" so that they can help others mitigate burnout.